SALING DUKUNG: KEMITRAAN KELUARGA DAN MASYARAKAT DENGAN MADRASAH - Matali Matali (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2018)
Education is one of the basic human needs. In line with that government and society established various educational institutions, one of which is Madrasah. Educational institutions are directly located in the midst of a community, thus making it an institution close to the family and community environment. This condition resulted in the emergence of close relationship or partnership between family and society with Madrasah. The background that causes the partnership is the existence of functional interdependence in order to realize the same goal, which is to provide education for the younger generation. Behavior of partnership between social system is not always in the form of formal system, but sometimes form of informal behavior among others is social and material contribution in the hope that more passionate teacher in carrying out its duty. Teachers can act as a culture broker that is the modernization agent because the teacher has the resources of mastery of science of religion as well as science and technology. Because the advantages of these teachers resulted in not a few teachers appreciated and occupied an important position in the social environment.